Real-time acceleration monitoring-based rapid earthquake response for ports in Korea. Issue 5 (4th July 2018) - Sun, Chang-Guk; Kim, Han-Saem; Cho, Hyung-Ik; Jeong, Byung-Sun
ABSTRACT: To establish viable earthquake counterplans for ports in Korea, data regarding earthquake motion on the ground and in buildings must be collected using acceleration monitoring systems. Acceleration monitoring-based strategies for port facilities are useful not only for ensuring rapid responses during and after earthquakes but also for regional data collection to assist reliable seismic design. Acceleration monitoring systems were installed at coastal facility sites in target ports, including a soil site to represent the facility and a rock site as a reference. The systematic earthquake alert software was designed to help them in decision-making about a possible seismic hazard and its reporting. The earthquake alert system was composed of two sequential functional software systems sharing an acceleration monitoring database applied to the target ports. The earthquake response software system triggers an alarm based on the peak ground acceleration per second computed from the monitored data. Then, the earthquake hazard estimation software system evaluates possible earthquake-induced site-specific geotechnical hazards linked to the peak ground acceleration. The integrated system was successfully operated and was able to rapidly provide an emergency report containing event records and geotechnical earthquake hazards during the September 2016 Gyeongju earthquake, the largest recorded earthquake in Korea.